Pelvic Nephroureterectomy for Renal Cell Carcinoma in an Ectopic Kidney. (22nd October 2012) - Baldie, Kevin G.; Al-Qassab, Usama A.; Ritenour, Chad W.; Issa, Muta M.; Osunkoya, Adeboye O.; Petros, John A.
Abstract : We present a case of an ectopic renal tumor in a 61-year-old morbidly obese man with a pelvic kidney found after presenting with hematuria and irritative voiding symptoms. The mass, along with the ectopic kidney and ureter, was radically resected through an open operation that involved removing both them and the renal vessels from the underlying iliac vessels. Pathological analysis demonstrated an 8.3 cm papillary renal cell carcinoma (RCC) with oncocytic features, Fuhrman nuclear grade 3, with angiolymphatic invasion and negative margins. The patient has been recurrence-free for over four years since tumor resection.